2022
DOI: 10.1016/j.ajic.2021.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Compared hand hygiene compliance among healthcare providers before and after the COVID-19 pandemic: A rapid review and meta-analysis

Abstract: Background Hand hygiene (HH) is a cost-effective measure to reduce healthcare-associated infections. The overall characteristics and changes of hand hygiene compliance (HHC) among healthcare providers during the COVID-19 pandemic provided evidence for targeted HH intervention measures. Aim To systematically review the literature and conduct a meta-analysis of studies investigating the rate of HHC and the characteristics of HH during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 43 publications
3
21
0
2
Order By: Relevance
“…Our study has demonstrated that during the COVID-19 pandemic all examined IPC measures improved compared with the situation prior to the pandemic. Previous studies also indicated advances in implementing IPC measures and better IPC compliance among healthcare workers (HCWs), both during COVID-19 [21,22] and other viral outbreaks [23,24]. It is expected that outbreak risk drives positive changes in IPC behaviors of healthcare workers (HCWs) due to fear and heightened awareness of the importance of adhering to IPC guidelines [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated that during the COVID-19 pandemic all examined IPC measures improved compared with the situation prior to the pandemic. Previous studies also indicated advances in implementing IPC measures and better IPC compliance among healthcare workers (HCWs), both during COVID-19 [21,22] and other viral outbreaks [23,24]. It is expected that outbreak risk drives positive changes in IPC behaviors of healthcare workers (HCWs) due to fear and heightened awareness of the importance of adhering to IPC guidelines [25].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline compliance of lower-middle and lower income countries was 29% [ 14 ]. Another systematic review showed the HH compliance from COVID-19 pandemic increased to 74% compared to pre-COVID pandemic studies [ 15 ]. The above compliance rates are comparable with our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review shows that during the pandemic period, nurses had the highest compliance rate of 80% (95% CI, 74%–87%) and auxiliary HCW had the lowest compliance rate of 70% (95% CI, 62%–77%) [ 15 ]. The study from south zone showed profession-specific HHAR was found to be highest among doctors (67.5%) and nurses (66.4%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the pandemic was variable according to structural and organizational factors, and variables associated with the waves of the pandemic. Moreover, the hospital procedures and organization which was specifically set up to address the pandemic, and more specifically the procedures used for the management of COVID-19-related acute respiratory failure (ARF) changed over time, for example, with a decrease in the use of invasive mechanical ventilation [30][31][32][33][34][35][36].…”
Section: Why the Covid-19 Pandemic Is Associated With A Higher Risk O...mentioning
confidence: 99%
“…There is a growing body of evidence suggesting that MDRO-related infections increased in SARS-CoV-2infected patients [85]. This raise, despite a low risk of cross-transmission of colonization related to the lockdown, could be explained by several factors such as an increased antibiotic pressure [86,87], a higher risk of cross-transmission related to overloaded healthcare workers, and by individual specific factors, such as specific procedures (i.e., prone positioning) [85,88], and others such as frequency and duration of exposure to invasive procedures, and immunosuppression [31][32][33].…”
Section: Antimicrobial Resistance and Sars-cov-2mentioning
confidence: 99%